Early loss of fixation after surgical treatment of distal radius fractures: Does the number of screws matter? - Schindelar, Lili (J Orthop, 2020)
Fixation methods in distal radius fractures has been studied biomechanically, but studies evaluating clinical correlation of that data are lacking. We hypothesize that the use of unthreaded pegs and decreased screw number would correlate with an early failure of fixation. There were 50 operatively treated distal radius fractures with initial post-operative radiographs that demonstrated loss of fixation. An age, BMI, and fracture-type matched cohort of 50 non-failed distal radius fractures was used for comparison. The average number of distal screws in the failed fixation group was 5.3 compared to 4.8 in the group with no loss of fixation (p = 0.07). The average number of proximal shaft screws used in the failed fixation group was 3.2 compared to 3.2 in the control group (p = 0.60). There was no difference between the use of pegs in either group. There was a significant difference between distal screw number between constructs that failed from distal screw pullout as compared to the control group, 5.6 vs. 4.8 (p = 0.0001). In conclusion, there was no difference in the number of proximal screws used in distal radius fractures that demonstrated loss of early fixation. Additionally, having more than five screws in the distal fragment had a higher rate of failure from distal screw pullout, however this was likely confounded by the more severe intra-articular fractures that had additional fixation applied in an attempt to increase stability. Finally, using smooth pegs or screws in the distal fragment made no difference in loss of fixation.